Nigerian Students, 1968 (1968)
Group portrait of Nigerian students. This photo is printed in the 1968 El Rodeo Yearbook with the title "Nigerian students" in the Clubs and Organizations section (pg. 60). The students appear to all be Cal Poly international students from Nigeria. Students: Bottom Row: Timothy Kowobari, Wilson Etuke, Olufunke Taiwo, Shola Onipede. Isaiah Ilori. Row 2: S. Oladiji, Garba Mohammed, Gbenedid John, Sunday Ebojoh. Row 3: Abdum Mohammed, Jocob Alere, Peter Akintola, Adekunle Taiwo, Mohammed Swartz